SUBJECTIVE CONSCIOUSNESS OF THE RAUDLATUL ATHFAL CHILDHOOD ON PLAYING (Phenomenological Pedagogy Exploration) - Imroatun, Imroatun (ACIECE, 2016)
Phenomenological pedagogy is an important school from Utrecht University, Netherland. They has an significant contribution in playing theory for raudlatul athfal who were aged at early childhood. Chronologically, this stream still have relevance to the vanguard of phenomenology, Edward Husserl. The school of Utrecht; through Kohnstam and Langeveld and other leaders; agreed to disseminate phenomenology as practical measures with a focus on subjective consciousness of the child as its predecessor, especially in the field of education. This school is still followed by educator in Indonesia through Langeveld’s, Beknopte Theoretische Pedagogiek